Electrical and Mechanical Analysis of Different TSV Geometries - Il Ho Jeong; Alireza Eslami Majd; Jae Pil Jung; Nduka Nnamdi Ekere (Metals, 2020)
Through-silicon via (TSV) is an important component for implementing 3-D packages and 3-D integrated circuits as the TSV technology allows stacked silicon chips to interconnect through direct contact to help facilitate high-speed signal processing. By facilitating the stacking of silicon chips, the TSV technology also helps to meet the increasing demand for high density and high performance miniaturized electronic products. Our review of the literature shows that very few studies have reported on the impact of TSV bump geometry on the electrical and mechanical characteristics of the TSV. This paper reports on the investigation of different TSV geometries with the focus on identifying the ideal shapes for improved electrical signal transmission as well as for improved mechanical reliability. The cylindrical, quadrangular (square), elliptical, and triangular shapes were investigated in our study and our results showed that the quadrangular shape had the best electrical performance due to good characteristic impedance. Our results also showed that the quadrangular and cylindrical shapes provided improved mechanical reliability as these two shapes lead to high Cu protrusion of TSV after the annealing process.